HUBUNGAN WORK ENGAGEMENT DAN ORGANIZATIONAL EFFICACY (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2016)
Abstrak.Penelitian ini bertujuan untuk menguji ada tidaknya hubungan work engagement dan organizational efficacy. Penelitian ini merupakan penelitian kuantitatif korelasional. Populasi penelitian ini adalah individu (karyawan) PT Yuro Mustika. Jumlah sampel yang digunakan dalam penelitian sejumlah 118 individu (karyawan). Teknik sampling yang dipakai yaitu incidental sampling. Data penelitian dihimpun menggunakan skala work engagement dan skala organizational efficacy. Skala organizational efficacy terdiri dari 43 aitem dengan koefisien daya beda aitem sebesar 0,308 sampai dengan 0,687 dan koefisien reliabilitas sebesar 0,910. Skala work engagement terdiri dari 32 aitem dengan koefisien daya beda aitem antara 0,318 sampai dengan 0,597 dan koefisien reliabilitas sebesar 0,881. Organizational efficacy individu (karyawan) PT Yuro Mustika berada dalam kategori sedang dengan aspek yang paling berpengaruh adalah sense of mission, future or purpose. Kondisi work engagement individu (karyawan) PT Yuro Mustika berada dalam kategori sedang dengan dimensi yang paling berpengaruh adalah vigor atau energi dan ketahanan mental ketika menghadapi sebuah hambatan dalam bekerja. Metode analisis dalam penelitian ini menggunakan teknik korelasi Product Moment dengan hasil koefisien korelasi sebesar (rxy) 0,485 dan nilai signifikansi sebesar 0,000 (p 0,01). Berdasarkan nilai koefisien tersebut, hipotesis “ada hubungan work engagement dan organizational efficacy” diterima.Abstract. This research’s purpose is to find out the correlation between work engagement and organizational efficacy. This is a correlational quantitative research with the company employees from PT Yuro Mustika as the population. The number of sample that used in this research is 118 persons. Using incidental technique as the sampling technique, this research data gathered with work engagement scale and organizational efficacy scale. Organizational efficacy scale consists of 43 items with coefficient validity per item in the amount of 0,308 to 0,687 and reliability coefficient in the amount of 0,910. Work engagement scale consists of 32 items with coefficient validity per item in the amount of 0,318 to 0,597 and reliability coefficient in the amount of 0,881. The individual organizational efficacy of the employees in PT Yuro Mustika include in the middle category with the most influences aspect called sense of mission, future or purpose. The individual work engagement condition of the employees in PT Yuro Mustika include in the middle category with the most influences dimension called vigor or energy and mental toughness in facing the working obstacles. The analysis method in this research using correlation technique Product Moment with correlation coefficient result in the number of (rxy) 0,479 and the point of significant is 0,000 (p 0,01). Based on the coefficient point above, the hypothesis “there is a correlation between work engagement and organizational efficacy” has been accepted. The higher work engagement the higher organizational efficacy too and so does the opposite, the lower work engagement the lower organizational efficacy.